2005
DOI: 10.1007/s00266-004-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Physiologic Advantages of Totally Subfacial Breast Implants

Abstract: For the past 4 years, whenever it was possible to choose between the subglandular or the submuscular location for the implant pocket (in cases with no precise indication for the submuscular location), the authors have opted for the totally subfascial plane (subaponeurotic) to avoid the disadvantages of the other locations and to obtain additional benefits. The subfascial plane lies below the deep thoracic fascia, or deep aponeurosis, which is not only that of the pectoralis (the muscle connecting with the brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
1
24
0
2
Order By: Relevance
“…10 As other investigators have observed, the fascia is a strong, distinct layer that can be easily identified on axillary approach. [22][23][24][25][26][27][28] This layer has a significant strength that becomes apparent during intraoperative manipulation, and when approximated, provides continuous fascial coverage over a round and anatomically shaped implant (Fig. 3).…”
Section: Axillary Approachmentioning
confidence: 98%
See 2 more Smart Citations
“…10 As other investigators have observed, the fascia is a strong, distinct layer that can be easily identified on axillary approach. [22][23][24][25][26][27][28] This layer has a significant strength that becomes apparent during intraoperative manipulation, and when approximated, provides continuous fascial coverage over a round and anatomically shaped implant (Fig. 3).…”
Section: Axillary Approachmentioning
confidence: 98%
“…3,4,10,41 Despite the reliability of the subglandular pocket, placing the silicone implant next to the glandular tissue may lead to an unsatisfactory result in terms of implant visibility, which is especially noticeable in thin patients with smaller breasts and soft-tissue coverage, whereby a sharp transition can be seen in the limits of the implant. [22][23][24][25][26][27][28] To improve aesthetic results, alternative surgical options for the implant pocket have been described. 3,4 Among these, the submuscular technique was first introduced to contribute optimal [17][18][19][20] ; however, the main drawbacks are implant distortion, morbidity, and postoperative pain.…”
Section: The Subfascial Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…En su porción caudal, sin embargo la disección de la superficie del músculo pectoral resulta ser relativamente fácil (8,9), encontrando ramas perforantes de muy pequeño calibre. La infiltración anestésica subfascial o intramuscular, reduce considerablemente la contracción muscular por la acción del electrocauterio mientras se realiza la disección y además facilita la hemostasia de los vasos perforantes menores.…”
Section: Anatomía Quirúrgicaunclassified
“…In subfascial breast augmentation, there had been reports of 0% to 2% of capsular contracture [1][2][3]8]. Graf et al mentioned a 2.3% of capsular contracture grade II in 263 patients that underwent subfascial breast augmentation [8].…”
Section: Introductionmentioning
confidence: 98%